Modeling and analysis of integrated wheel hub. Issue 1 (1st April 2022) - Shah, Vyom; Patel, Pavan; Keshav, Manjeet
Abstract: The main objective of the hub is to act as a support structure to the entire wheel assembly of the vehicle. It is designed to absorb and dissipate the kinetic energy from the impact on the tire. This paper discusses an idea for optimizing the wheel assembly by redesigning, validating the design through analysis, material selection and overall weight reduction. The design optimization is done while taking in consideration of the design constraints, factor of safety (FOS) and manufacturability through conventional means. Weight reduction in the wheel assembly will help improve the suspension performance. The research is based on integrating parts of the wheel assembly for weight reduction, performance optimization and ease of assembly. The proposed design of wheel flange will be followed by material selection for attaining an adequate FOS and wear strength.